2010
DOI: 10.1192/pb.bp.109.026849
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of depot antipsychotics in routine clinical practice

Abstract: Aims and methodTo compare effectiveness of long-acting injections in schizophrenia and related psychoses in Lanarkshire, Scotland, from 2002 to 2008. We retrospectively assigned Clinical Global Impression (CGI) scores and examined discontinuation and hospitalisation rates.ResultsRisperidone, zuclopenthixol and flupentixol were associated with CGI improvement in 72-74% of individuals. Zuclopenthixol was associated with lower rates of discontinuation as a result of inefficacy compared with risperidone (hazard ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
11
0
2
Order By: Relevance
“…The result is at odds with the only randomized head-to-head comparison that has been performed for these drugs [Rubio et al 2006], in which risperidone LAI performed better on several measures, including the PANSS total score. A retrospective observational study [Shajahan et al 2010], however, that compared several LAIs (risperidone, zuclopenthixol and flupenthixol) found longer time to discontinuation and lower hospitalization rates for patients treated with zuclopenthixol LAI. Also relevant is the finding in a large effectiveness study that another medium-potent oral FGA (perphenazine) was found to have a comparable effectiveness to several SGAs [Lieberman et al 2005].…”
Section: Lai Antipsychotics Versus Olanzapine Oralmentioning
confidence: 99%
“…The result is at odds with the only randomized head-to-head comparison that has been performed for these drugs [Rubio et al 2006], in which risperidone LAI performed better on several measures, including the PANSS total score. A retrospective observational study [Shajahan et al 2010], however, that compared several LAIs (risperidone, zuclopenthixol and flupenthixol) found longer time to discontinuation and lower hospitalization rates for patients treated with zuclopenthixol LAI. Also relevant is the finding in a large effectiveness study that another medium-potent oral FGA (perphenazine) was found to have a comparable effectiveness to several SGAs [Lieberman et al 2005].…”
Section: Lai Antipsychotics Versus Olanzapine Oralmentioning
confidence: 99%
“…In addition, clinical global impression scale (CGI) [10] severity and improvement subscales were retrospectively assigned at the time of initial detoxification, and after 2 years. Such retrospective assignment has been performed by others in assessing treatment response [11]. Patient records were examined by scrutinising case records and computer based patient information systems to monitor subsequent progress over a 2 year period.…”
Section: Methodsmentioning
confidence: 99%
“…La evidencia de si los APD aumentan la adherencia y disminuyen las recaí-das y rehospitalizaciones no es consistente 3,[7][8][9] . Hay estudios que muestran que los APD pueden aumentar la tasa de adherencia en pacientes con esquizofrenia 7,10 , pero el aumento de adherencia no necesariamente se refleja en una disminución significativa de las tasas de recaída o rehospitalización en el largo plazo 9 .…”
Section: Introductionunclassified